TGF-ß alterations in oral squamous cell carcinoma. Narrative review. - Jorge Candia; Carolina Somarriva; Diego Fonseca; Fernando Parada; Jorge Briceño; Alejandra Fernández (Universidad de Concepción., 2016)
The transforming growth factor beta (TGF-ß) is a cytokine that plays crucial roles in the regulation of angiogenesis, immune response, proliferation, migration and apoptosis of cells. In addition, it can inhibit cell progression and stimulate apoptosis in early stages of cancer. TGF-ß is a multifunctional homodimeric protein secreted by various cell lines, which have three different isoforms: TGF-ß1, TGF-ß2 and TGF-ß3. In normal conditions, TGF-ß1 activates some tumor suppressor cell signaling pathways that inhibit proliferation and are involved in cell migration, differentiation and apoptosis. However, in more advanced stages of cancer, when TGF-ß1 is altered, it acts as a promoter of tumorigenesis and may cause: 1) increased TGF-ß1, 2) overexpression of TGF-ß1 receptors (TßR), 3) TßR mutations, and 4) downregulation of TGF-beta receptor. In oral squamous cell carcinoma, the path is altered especially at the level of transmembrane receptors, with the TßR-II and TßR-III subtypes being the most affected. However, there is little information on the prognostic role it plays in the various types of cancers. It is important to study the signaling pathways of TGF-ß in order to develop techniques that may help detect their alterations and restore their normal operation. The objective of this review is to describe the alterations of TGF-ß in oral squamous cell carcinoma.